2010
DOI: 10.1002/art.27220
|View full text |Cite
|
Sign up to set email alerts
|

A four‐gene biomarker predicts skin disease in patients with diffuse cutaneous systemic sclerosis

Abstract: Objective. Improved outcome measures in systemic sclerosis (SSc) are critical to finding active therapeutics for this disease. The modified Rodnan skin thickness score (MRSS) is the current standard for evaluating skin disease in SSc, but it is not commonly used in the clinical setting, in part because it requires specialized training to perform accurately and consistently. The purpose of this study was to investigate whether skin gene expression might serve as a more objective surrogate outcome measure to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
134
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 27 publications
(35 reference statements)
12
134
3
Order By: Relevance
“…In scleroderma, serum COMP has been reported to be significantly higher than normal controls 30 and correlate to skin involvement as measured by modified Rodnan total skin thickness score. 25,28 Moreover, a pathogenic role of COMP in scleroderma has been reported. [25][26][27][28]30 By the gene expression profiling of cultured skin fibroblasts, COMP mRNA level is elevated in scleroderma fibroblasts and COMP protein accumulates in scleroderma, but not normal skin by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In scleroderma, serum COMP has been reported to be significantly higher than normal controls 30 and correlate to skin involvement as measured by modified Rodnan total skin thickness score. 25,28 Moreover, a pathogenic role of COMP in scleroderma has been reported. [25][26][27][28]30 By the gene expression profiling of cultured skin fibroblasts, COMP mRNA level is elevated in scleroderma fibroblasts and COMP protein accumulates in scleroderma, but not normal skin by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…25,28 Moreover, a pathogenic role of COMP in scleroderma has been reported. [25][26][27][28]30 By the gene expression profiling of cultured skin fibroblasts, COMP mRNA level is elevated in scleroderma fibroblasts and COMP protein accumulates in scleroderma, but not normal skin by immunohistochemistry. 26 Cultured scleroderma fibroblasts express higher amount of COMP than normal controls and further TGF-␤1 induces a large increase of COMP mRNA and protein in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the key cells depositing the excess amounts of ECM that are characteristic of fibrosis (Hinz et al, 2012;Tomasek et al, 2002). COMP is produced by myofibroblasts in systemic sclerosis and has reached diagnostic relevance as one component of a four-gene signature that is typically seen in individuals with systemic sclerosis (Farina et al, 2010(Farina et al, , 2009. We have also shown that high COMP levels are not restricted to fibrosis occurring in systemic sclerosis but that high levels also occur also in the fibrotic stroma adjacent to epidermal tumors as well as in the fibrosis underlying chronic non-healing ulcers (Agarwal et al, 2013), all characterized by overproduction of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…It includes two TFG-β-regulated genes: cartilage oligomeric matrix protein (COMP) and thrombospondin-1 (THS1), and two interferon (IFN)-regulated genes: interferon-induced 44 (IFI44) and sialoadhesin (SIG1). The central hypothesis is that if IL-1 is a key cytokine leading to fibrosis in SSc, its inhibition will downregulate the expression of the 4-gene biomarker in the skin [30,31].…”
Section: Interleukin-1mentioning
confidence: 99%